2008
DOI: 10.1007/s11671-008-9221-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Porous NiO and ZnO Submicro- and Nanofibers from Electrospun Polymer Fiber Templates

Abstract: Porous nickel oxide (NiO) and zinc oxide (ZnO) submicro- and nanofibers were synthesized by impregnating electrospun polyacrylonitrile (PAN) fiber templates with corresponding metal nitrate aqueous solutions and subsequent calcination. The diameter of the NiO and ZnO fibers was closely related to that of the template fibers and larger diameters were obtained when using the template fibers with larger diameter. SEM results showed that the NiO and ZnO fibers have a large amount of pores with diameters ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…The first peak at 26°cor-responds to carbon while the other two peaks at 37°and 43°a re NiO (111) and NiO (200), respectively. These results are in good agreement with those available in literature [27][28][29][30][31][32].…”
Section: Resultssupporting
confidence: 92%
“…The first peak at 26°cor-responds to carbon while the other two peaks at 37°and 43°a re NiO (111) and NiO (200), respectively. These results are in good agreement with those available in literature [27][28][29][30][31][32].…”
Section: Resultssupporting
confidence: 92%
“…Among such oxides, NiO is of particular interest owing to its high theoretical specific capacitance of 2573 F/g [22,23], high chemical/thermal stability, ready availability, environmentally benign nature and lower cost as compared to the state-of-the-art supercapacitor material RuO 2 [24,25]. There have been a variety of reports of the synthesis of different NiO nanostructures including porous nano/microspheres [26], nanoflowers [27], nanosheets [28], and nanofibers [29]. It has been shown that the electrochemical performance of NiO nanocrystals largely depends on its microstructure, surface area, and the presence of dopants [30][31][32][33][34][35], suggesting that the development of controlled syntheses of NiO nanostructures with the desired features, e.g., high electronic conductivity, low diffusion resistance to protons/cations, and high electroactive area is of paramount importance.…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructures and heterostructures made of ZnO have already been used as a transparent conductor in solar cells, varistors and sensors [7,8]. Recently, ZnO nanostructures have draw attentions for possible applications in optoelectronic devices such as nanostructured solar cells, ultra sensitive optical fiber sensors and UV laser diodes [9][10][11]. ZnO nanostructures are required to have high crystalline quality for most applications.…”
Section: Introductionmentioning
confidence: 99%